(untitled) (Revista do Centro de Estudos Portugueses, 2008)
Este texto relata as duas visitas que Lúcio Cardoso faz a Mangaratiba, no Estado do Rio de Janeiro. This text reports two visits which Lúcio Cardoso does the Mangaratiba, in the State of the Rio de Janeiro.